Effects of First Dimension Eluent Composition in Two-dimensional Liquid Chromatography - Li, Xiaoping (2011)
Comprehensive two-dimensional liquid chromatography (LCxLC) has received a great deal of attention during the past few years because of its extraordinary resolving power. The biggest advantage of this technique is that very high peak capacities can be generated in a relatively short time. Numerous approaches to maximize the peak capacity in LCxLC have been employed. In this work we investigate the impact of the first dimension mobile phase on selectivity. LCxLC has several potential advantages over one-dimensional LC (1DLC) in that unconventional solvents, at least in reversed-phase LC, can be used. For example, solvents which strongly adsorb in the UV in the first dimension are not problematic in LCxLC. This so because the UV detector is placed after the second dimensional column, as pulses of the first dimension eluent arrive at the second dimensional column, they elute well before the solutes of interest and therefore do not interfere at all with detection of solute peaks. So far, the most widely used solvents in reversed-phase 1DLC are methanol and acetonitrile. However, the “UV advantage” of 2DLC allows us to employ UV active solvents, such as acetone. We compare their differential selectivities to that of acetonitrile for the separation of 23 indole acetic acids of interest in plant biology. We also apply them to the separation of a maize seed extract, a very complex sample. In both sample sets, mobile phase composition can be an important parameter to increase the orthogonality of the two dimensions and thus, to increase the effective peak capacity of LCxLC.